UMP Holdings personnel prepared 1000 face shield for frontliners - UMP, PNC (2020)
Concerned about the need for face protection for health and frontline workers struggling to combat the spread of the Covid-19 outbreak especially in Pahang state, UMP Holdings Sdn. Bhd. (UMPH), which is a subsidiary of Universiti Malaysia Pahang (UMP), lent a helping hand by providing 1,000 face shields at its office building on April 13, 2020.